2021
DOI: 10.3390/genes12091363
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Brain Gene Expression Data from Mouse Model Studies of Maternal Immune Activation Using Poly(I:C)

Abstract: Maternal immune activation (MIA) is a known risk factor for schizophrenia (SCZ) and autism spectrum disorder (ASD) and is often modelled in animal studies in order to study the effect of prenatal infection on brain function including behaviour and gene expression. Although the effect of MIA on gene expression are highly heterogeneous, combining data from multiple gene expression studies in a robust method may shed light on the true underlying biological effects caused by MIA and this could inform studies of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…Several epidemiological studies have indicated an association between maternal bacterial and viral infections (e.g., maternal influenza infection) during pregnancy and an increased incidence of schizophrenia in the offspring after puberty ( Shi et al, 2003 ; Meyer et al, 2005 ; Solek et al, 2018 ). A recent meta-analysis showed that the expression of genes linked to schizophrenia and other neurodevelopmental diseases is dysregulated in maternal immune activation (MIA) mouse models ( Laighneach et al, 2021 ). Recently, the potential of P2X7Rs as treatment targets for schizophrenia was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have indicated an association between maternal bacterial and viral infections (e.g., maternal influenza infection) during pregnancy and an increased incidence of schizophrenia in the offspring after puberty ( Shi et al, 2003 ; Meyer et al, 2005 ; Solek et al, 2018 ). A recent meta-analysis showed that the expression of genes linked to schizophrenia and other neurodevelopmental diseases is dysregulated in maternal immune activation (MIA) mouse models ( Laighneach et al, 2021 ). Recently, the potential of P2X7Rs as treatment targets for schizophrenia was examined.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent evidences have underlined the potential critical role of Sema 3A in fostering these alterations [7,14,57]. An increasing number of epidemiological studies are stressing the significance of maternal inflammation in the onset of autism or schizophrenia [58][59][60][61]. In particular, prenatal exposure to infections have been described as causative factor in rise of schizophrenic births [62].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of epidemiological studies are stressing the significance of maternal inflammation in the onset of autism or schizophrenia [ 58 61 ]. In particular, prenatal exposure to infections have been described as causative factor in rise of schizophrenic births [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides direct impacts on the fetal brain, transcriptomic alterations in adult brain after prenatal exposure of adverse events were reported in animal studies. For example, transcriptomic profiling on adult cortex [46,49,50], amygdala [51], and nucleus accumbens [50] in the animal model of maternal immune activation (MIA) identified many gene pathways critical for neurodevelopmental processes, including important genes associated with schizophrenia (SCZ), autism spectrum disorder (ASD) and cognitive phenotypes [52].…”
Section: Introductionmentioning
confidence: 99%